Modern development of artificial intelligence technologies and problems of legal regulation of profiling and targeted advertising in Kazakhstan - Akhmetova, S.B.; Kassymzhanova, A.A.; Ibrayeva, A.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In 2023, Kazakhstan adopted the Law ‘On Online Platforms and Online Advertising’, aiming to control online advertising. The law does not fully protect personal data during profiling and targeted advertising, being limited to general norms of legislation on the protection of personal data. Moreover, Kazakhstani laws vaguely regulate the automated collection, analysis and processing of data, which form the basis of profiling, microtargeting and artificial intelligence technologies. The article compares Kazakhstani and European regulations of profiling and targeted advertising. We consider the opinions of Western scholars on how profiling and targeted advertising invade a person’s privacy, autonomy, and freedom, and pose threats to other fundamental rights and freedoms of the individual. The article critically assesses the lack of adequate regulation of profiling and targeted advertising in Kazakhstani law on the protection of personal data. A comparative analysis of the problem with European legislation leads to the conclusion that Kazakhstani legislators should take seriously the scope and complexity of the right to privacy as well as how it relates to other rights and freedoms. The nation requires a high-quality law that safeguards personal data during profiling and targeted advertising, providing for clear responsibilities of owners and operators of personal databases.